[99mTc]Tc-PSMA-T4—Novel SPECT Tracer for Metastatic PCa: From Bench to Clinic - Maurin, Michał; Wyczółkowska, Monika; Sawicka, Agnieszka; Sikora, Arkadiusz Eugeniusz; Karczmarczyk, Urszula; Janota, Barbara; Radzik, Marcin; Kłudkiewicz, Dominik; Pijarowska-Kruszyna, Justyna; Jaroń, Antoni; Wojdowska, Wioletta; Garnuszek, Piotr (Molecules (Basel, Switzerland), 2022)
Despite significant advances in nuclear medicine for diagnosing and treating prostate cancer (PCa), research into new ligands with increasingly better biological properties is still ongoing. Prostate-specific membrane antigen (PSMA) ligands show great potential as radioisotope carriers for the diagnosis and therapy of patients with metastatic PCa. PSMA is expressed in most types of prostate cancer, and its expression is increased in poorly differentiated, metastatic, and hormone-refractory cancers; therefore, it may be a valuable target for the development of radiopharmaceuticals and radioligands, such as urea PSMA inhibitors, for the precise diagnosis, staging, and treatment of prostate cancer. Four developed PSMA-HYNIC inhibitors for technetium-99m labeling and subsequent diagnosis were subjected to preclinical in vitro and in vivo studies to evaluate and compare their diagnostic properties. Among the studied compounds, the PSMA-T4 (Glu-CO-Lys-L-Trp-4-Amc-HYNIC) inhibitor showed the best biological properties for the diagnosis of PCa metastases. [99mTc]Tc-PSMA-T4 also showed effectiveness in single-photon emission computed tomography (SPECT) studies in humans, and soon, its usefulness will be extensively evaluated in phase 2/3 clinical trials.